Evaluation of the performance of 25 SARS-CoV-2 serological rapid diagnostic tests using a reference panel of plasma specimens at the Uganda Virus Research Institute. (November 2021) - Lutalo, Tom; Nalumansi, Aminah; Olara, Denis; Kayiwa, John; Ogwang, Bernard; Odwilo, Emmanuel; Watera, Christine; Balinandi, Stephen; Kiconco, Jocelyn; Nakaseegu, Joweria; Serwanga, Jennifer; Kikaire, Bernard; et al.
Highlights: ● This study identified the best performing rapid diagnostic kits for the detection of COVID-19 antibodies. ● A characterized reference panel of specimens was used to evaluate the serological kits. ● For IgM/IgG, Autobio, MultiG, and Standard Q had sensitivity and specificity ≥98%. ● For IgG, Boson, MultiG, Standard Q, and VivaDiag had sensitivity and specificity ≥98%. ● Serological testing will help better understand the epidemiology of the virus. Abstract: Introduction: Serological testing is needed to better understand the epidemiology of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Rapid diagnostic tests (RDTs) have been developed to detect specific antibodies, IgM and IgG, to the virus. The performance of 25 of these RDTs was evaluated. Methods: A serological reference panel of 50 positive and 100 negative plasma specimens was developed from SARS-CoV-2 PCR and antibody positive patients and pre-pandemic SARS-CoV-2-negative specimens collected in 2016. Test performance of the 25 RDTs was evaluated against this panel. Results: A total of 10 RDTs had a sensitivity ≥98%, while 13 RDTs had a specificity ≥98% to anti-SARS-CoV-2 IgG antibodies. Four RDTs (Boson, MultiG, Standard Q, and VivaDiag) had both sensitivity and specificity ≥98% to anti-SARS-CoV-2 IgG antibodies. Only three RDTs had a sensitivity ≥98%, while 10 RDTs had a specificity ≥98% to anti-SARS-CoV-2 IgM antibodies. Three RDTs (Autobio, MultiG, and Standard Q) had sensitivity and specificity ≥98% to combined IgG/IgM. The RDTs that performed well also had perfect or almost perfect inter-reader agreement. Conclusions: This evaluation identified three RDTs with a sensitivity and specificity to IgM/IgG antibodies of ≥98% with the potential for widespread antibody testing in Uganda.